Self-repairing polyurea coating as well as preparation method and application thereof

By using raw materials such as polyurea prepolymers and chain extenders to prepare self-healing polyurea coatings, and combining phytic acid and polyethyleneimine, a super-hydrophilic composite coating is constructed, which solves the problem of anti-fouling of existing oil-water separation materials. To solve the problems of poor performance and poor durability, an oil-water separation membrane with high anti-fouling properties and self-healing function has been realized.

CN119331494AActive Publication Date: 2025-01-21BEIFANG UNIV OF NATITIES
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411680444.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-21
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The existing oil-water separation materials have poor soil resistance, poor durability, and lack of super-hydrophilic self-healing coating materials during oil-water separation.

Method used

The self-healing polyurea coating is composed of polyurea prepolymer, solvent, chain extender and other raw materials in specific proportions, and through the combination of phytic acid and polyethyleneimine, a super-hydrophilic composite coating with six hydrogen bonds is constructed , to achieve the self-healing function of the coating.

Benefits of technology

It improves the anti-fouling and durability of the oil-water separation membrane, realizes the function of self-repair after damage, and enhances the material's resistance to damage and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331494A_ABST
    Figure CN119331494A_ABST
Patent Text Reader

Abstract

The invention discloses a self-repairing polyurea coating as well as a preparation method and application thereof, and the self-repairing polyurea coating comprises the following raw materials: a polyurea prepolymer, a solvent and a chain extender in a ratio of (20-60): (15-40): (5-30), the polyurea prepolymer is prepared from the following raw materials: a solvent, an amino-terminated substance, an isocyanate-terminated substance and an organic tin catalyst in a ratio of (10-25): (10-30): (20-60): (0.1-1). The self-repairing polyurea coating disclosed by the invention has better mechanical properties, hydrogen bonds are damaged at a certain temperature, dynamic disulfide bonds show a free movement and fusion trend so as to complete healing, and after the coating is recovered to room temperature, the hydrogen bonds are reconstructed to lock the disulfide bonds again, so that the self-repairing polyurea coating has a good self-repairing effect. And the oil-water separation membrane has a self-repairing function after being damaged while having damage resistance, so that the durability of the material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new materials and surface technology, and in particular relates to a self-repairing polyurea coating and a preparation method and application thereof. Background Art

[0002] With the development of industry, oily wastewater is seriously threatening human survival and the surrounding environment. Therefore, people are paying more and more attention to the field of oil-water separation. Membrane separation technology is the most energy-saving, environmentally friendly and efficient of the many existing separation methods, and a water film will be formed during the separation process to give it good anti-fouling properties. Existing solutions mostly use natural products and their derivatives to construct special wetting surfaces, but most natural product coatings have poor mechanical properties. During the oil-water separation process, they are difficult to withstand long-term scratches and have poor durability.

[0003] Materials such as polyurea and polyurethane are widely used in other fields such as construction due to their excellent waterproof, wear-resistant and corrosion-resistant properties. Polyurea, polyurethane and other materials are mostly used in the form of foam, sponge and the like for oil-water separation, but the separation effect is not good. Although the foam form is prepared in a simple foaming form, it is difficult to have good anti-fouling and mechanical properties in the field of oil-water separation. The sponge form mostly exists in the form of a substrate, and has the disadvantages of poor anti-fouling and high energy consumption. The prepared materials are also mostly hydrophobic and lipophilic, which further weakens the anti-fouling property of the material, thereby affecting the durability of the material.

[0004] Polyurea and polyurethane coatings have been well applied in many fields, but there are few reports in the field of oil-water separation, and there is little research on the convenient preparation method of coating. This may be because polyurea will be slightly damaged during long-term use. If the self-repairing ability of polyurea is poor, the tiny damage cannot be repaired in time, and it will gradually accumulate, resulting in a decrease in coating performance, damaging the oil-water separation effect of the coating and reducing the separation efficiency. The wettability of existing oil-water separation materials with self-repairing ability is also mostly hydrophobic and oleophilic. For example: the Chinese invention patent with publication number CN104984564A and publication date October 21, 2015 discloses a self-repairable oil-water separation material and its preparation method. On the basis of traditional polyurethane synthesis, fluorine-containing monomers and alkyl-containing monomers are introduced respectively to synthesize fluorine-containing N-substituted polyurethanes and alkyl-containing N-substituted polyurethanes, and the two are mixed in a certain proportion, and co-spinning is performed to obtain the oil-water separation material (oil-water separation membrane) of this invention. The oil-water separation material of this invention has strong oil-water separation ability and high separation efficiency; and the oil-water separation material of this invention has very excellent self-repairing performance. However, the material prepared by this invention patent is hydrophobic and oleophilic, and has disadvantages such as poor anti-fouling properties, and the preparation of the material requires complex steps such as blending and spinning.

[0005] Oleophilic separation materials have fatal weaknesses such as poor anti-fouling properties, while self-healing oil-water separation materials with super hydrophilicity are rarely reported. The preparation of self-healing oil-water separation coating materials with super hydrophilicity remains a challenge. Summary of the invention

[0006] The purpose of the present invention is to provide a self-repairing polyurea coating and a preparation method and application thereof.

[0007] In order to solve the problems existing in the prior art, the technical solution adopted by the present invention is:

[0008] In a first aspect, the present invention provides a self-repairing polyurea coating, which is composed of the following raw materials in the following ratios: polyurea prepolymer: solvent: chain extender = 20-60: 15-40: 5-30;

[0009] The polyurea prepolymer is composed of the following raw materials in the following proportions:

[0010] Solvent: amino-terminated substance: isocyanate-terminated substance: organotin catalyst = 10-25: 10-30: 20-60: 0.1-1.

[0011] Preferably, the solvent is dimethylformamide.

[0012] Preferably, the chain extender is 4,4'-diaminodiphenyl disulfide and oxalyl dihydrazide, and the molar ratio of the 4,4'-diaminodiphenyl disulfide to oxalyl dihydrazide is 3-9:1-7.

[0013] Preferably, the amino-terminated substance is a polyetheramine.

[0014] Preferably, the terminal isocyanate substance is isophorone diisocyanate.

[0015] Preferably, the organotin catalyst is dibutyltin dilaurate.

[0016] In a second aspect, the present invention provides a method for preparing the polyurea coating according to the first aspect, comprising the following steps:

[0017] ① Add terminal amino substances and terminal isocyanate substances to dimethylformamide in sequence, and finally add an organic tin catalyst, and stir in a water bath at 30-60°C for 0.5-3h to obtain a polyurea prepolymer with a long chain structure terminated with an isocyanate group;

[0018] ② Add dimethylformamide to the polyurea prepolymer, then add a chain extender, and stir in a water bath at 30-60°C for 1-5 hours to obtain a polyurea coating.

[0019] In a third aspect, the present invention provides a self-repairing oil-water separation membrane, which is obtained by compounding the polyurea coating described in the first aspect with a substrate.

[0020] In a fourth aspect, the present invention provides a method for preparing the oil-water separation membrane according to the third aspect, comprising the following steps:

[0021] ① dilute the polyurea coating according to any one of claims 1 to 6 to 5-30wt%, evenly apply it on the substrate, and dry it;

[0022] ② Place in 1-5wt% phytic acid aqueous solution and perform ultrasonic assembly for 10-30min,

[0023] ③ Add 1-5wt% FeCl3 aqueous solution with a volume of 1 / 2-1 / 10 of the phytic acid aqueous solution, continue ultrasonic assembly for 10-30 minutes, and then use deionized water to rinse off the unreacted chemicals;

[0024] ④ Place in a 1-5wt% polyethyleneimine aqueous solution and stir for 1-5h, rinse off unreacted chemicals with deionized water, and dry.

[0025] In a fifth aspect, the present invention provides application of the self-repairing oil-water separation membrane described in the fourth aspect in the field of oil-water separation.

[0026] The advantages and beneficial effects of the present invention are:

[0027] 1. The self-healing polyurea coating of the present invention uses 4,4'-diaminodiphenyl disulfide (AD) and oxalyl dihydrazide (ODH) with dynamic disulfide bonds as chain extenders, and constructs unique six-fold hydrogen bonds while constructing double hydrogen bonds. The dynamic disulfide bonds show a tendency to move freely and fuse at a certain temperature to complete the healing. Through the cooperation of metal coordination bonds, hydrogen bonds and other effects of phytic acid (PA) and polyethyleneimine (PEI), the entire coating is endowed with self-healing properties. And the unique six-fold hydrogen bonds constructed can use hierarchical hydrogen bonds at room temperature to limit the free movement of dynamic disulfide bonds, so that the coating has better mechanical properties. At a certain temperature, the hydrogen bonds are destroyed, and the dynamic disulfide bonds show a tendency to move freely and fuse to complete the healing. After returning to room temperature, the hydrogen bonds are reconstructed to lock the disulfide bonds again, so that the oil-water separation membrane has the ability to resist destruction while having a self-healing function after being destroyed, further improving the durability of the material.

[0028] 2. Since the present invention uses polyurea and hydrophilic substances such as phytic acid and polyethyleneimine to construct a super hydrophilic composite coating, the self-healing polyurea component itself has high wear resistance and self-healing properties, and the prepared separation material is super hydrophilic, thus giving the oil-water separation membrane high durability and high anti-fouling properties, and is suitable for various complex oil-water separation environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1The infrared spectrum of the sample obtained in each step of Example 4; wherein:

[0030] SSM is the original stainless steel mesh;

[0031] SSM@SHPU is a stainless steel mesh coated with SHPU coating;

[0032] SSM@SHPU@PA is SSM@SHPU after ultrasonic assembly treatment;

[0033] SSM@SHPU@PA@PEI is SSM@SHPU@PA treated with PEI;

[0034] Figure 2 This is a graph showing the circulating separation efficiency of the self-repairing oil-water separation membrane of the present invention for kerosene / water mixture;

[0035] Figure 3 The oil-water separation efficiency diagram of different material samples for different oil-water mixtures;

[0036] Figure 4 The oil-water separation flux diagram of different material samples for different oil-water mixtures;

[0037] Figure 5 This is a flow chart of self-repair performance testing. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present application to clearly describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments in the present application belong to the scope of protection of this application.

[0039] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0040] Example 1

[0041] This embodiment provides a method for preparing a self-healing polyurea coating (SHPU), comprising the following steps:

[0042] ① Preparation of polyurea prepolymer: Add 20 ml of dimethylformamide (DMF) into a three-necked flask as a solvent, then add 10 mmol of amino-terminated polyetheramine (D2000) and 20 mmol of isophorone diisocyanate (IPDI) in sequence, and finally add 0.13 g of dibutyltin dilaurate DBTDL as a catalyst. Stir for 1 hour in a 30°C water bath to obtain a polyurea prepolymer with a long chain structure terminated with an isocyanate group.

[0043] ② Add 30 ml of DMF to 41.93 g of polyurea prepolymer to reduce its viscosity, then add 10 mmol of chain extender, and stir in a water bath at 50°C for 3 hours to obtain a self-healing polyurea coating (SHPU). The chain extender is composed of oxalyl dihydrazide (ODH) and 4,4'-diaminodiphenyl disulfide (AD), wherein the ratio of the amount of oxalyl dihydrazide to 4,4'-diaminodiphenyl disulfide is 5:5.

[0044] Example 2

[0045] This embodiment provides a method for preparing a self-healing (SHPU) polyurea coating. The only difference between this embodiment and Example 1 is that the ratio of the amount of oxalyl dihydrazide and 4,4'-diaminodiphenyl disulfide (AD) is different. In this embodiment, the ratio of the amount of oxalyl dihydrazide to 4,4'-diaminodiphenyl disulfide is 3:7, and the rest is the same as Example 1.

[0046] Example 3

[0047] This embodiment provides a method for preparing a self-healing (SHPU) polyurea coating. The only difference between this embodiment and Example 1 is that the ratio of the amount of oxalyl dihydrazide and 4,4'-diaminodiphenyl disulfide (AD) is different. In this embodiment, the ratio of the amount of oxalyl dihydrazide to 4,4'-diaminodiphenyl disulfide is 1:9, and the rest is the same as Example 1.

[0048] Example 4

[0049] This embodiment provides a method for preparing a self-healing (SHPU) polyurea coating. The only difference between this embodiment and Example 1 is that the ratio of the amount of oxalyl dihydrazide and 4,4'-diaminodiphenyl disulfide (AD) is different. In this embodiment, the ratio of the amount of oxalyl dihydrazide to 4,4'-diaminodiphenyl disulfide is 7:3, and the rest is the same as Example 1.

[0050] Example 5

[0051] This embodiment provides a method for preparing a self-healing (SHPU) polyurea coating. The only difference between this embodiment and Example 1 is that the ratio of the amount of oxalyl dihydrazide and 4,4'-diaminodiphenyl disulfide (AD) is different. In this embodiment, the ratio of the amount of oxalyl dihydrazide to 4,4'-diaminodiphenyl disulfide is 9:1, and the rest is the same as Example 1.

[0052] Example 6

[0053] This embodiment provides a method for preparing a self-healing (SHPU) polyurea coating, comprising the following steps:

[0054] ① Preparation of polyurea prepolymer: Add 10 ml of dimethylformamide (DMF) into a three-necked flask as a solvent, then add 30 mmol of amino-terminated polyetheramine (D2000) and 60 mmol of isophorone diisocyanate (IPDI) in sequence, and finally add 1 g of dibutyltin dilaurate DBTDL as a catalyst. Stir for 1 hour in a 30°C water bath to obtain a polyurea prepolymer with a long chain structure terminated with an isocyanate group.

[0055] ② Add 40 ml of DMF to 60 g of polyurea prepolymer to reduce its viscosity, then add 30 mmol of chain extender, and stir in a water bath at 50°C for 3 hours to obtain a self-healing polyurea coating (SHPU). The chain extender is composed of oxalyl dihydrazide (ODH) and 4,4'-diaminodiphenyl disulfide (AD), and the ratio of the amount of oxalyl dihydrazide to 4,4'-diaminodiphenyl disulfide is 5:5.

[0056] Example 7

[0057] This embodiment provides a method for preparing a self-healing (SHPU) polyurea coating, comprising the following steps:

[0058] ① Preparation of polyurea prepolymer: Add 25 ml of dimethylformamide (DMF) into a three-necked flask as a solvent, then add 20 mmol of amino-terminated polyetheramine (D2000) and 40 mmol of isophorone diisocyanate (IPDI) in sequence, and finally add 0.1 g of dibutyltin dilaurate DBTDL as a catalyst. Stir for 1 hour in a 30°C water bath to obtain a polyurea prepolymer with a long chain structure terminated with an isocyanate group.

[0059] ② Add 15 ml of DMF to 20 g of polyurea prepolymer to reduce its viscosity, then add 20 mmol of chain extender, and stir in a water bath at 50°C for 3 hours to obtain a self-healing polyurea coating (SHPU). The chain extender is composed of oxalyl dihydrazide (ODH) and 4,4'-diaminodiphenyl disulfide (AD), and the ratio of the amount of oxalyl dihydrazide to 4,4'-diaminodiphenyl disulfide is 5:5.

[0060] Comparative Example 1

[0061] This comparative example provides a method for preparing a self-healing (SHPU) polyurea coating. The difference between this comparative example and Example 1 is only that a different chain extender is used. The chain extender in this comparative example is only oxalyl dihydrazide, and the rest is the same as Example 1.

[0062] Comparative Example 2

[0063] This comparative example provides a method for preparing a self-healing (SHPU) polyurea coating. The difference between this comparative example and Example 1 is only the amount of the chain extender used. The amount of the chain extender used in this comparative example is 40 mmol, and the rest is the same as Example 1.

[0064] Comparative Example 3

[0065] The difference between this comparative example and Example 1 is that the chain extender used is different. The chain extender in this comparative example is only 4,4'-diaminodiphenyl disulfide, and the rest is the same as Example 1.

[0066] Example 8

[0067] This embodiment provides a self-repairing oil-water separation membrane, which is prepared by the following method:

[0068] ① First, use ethanol, acetone and deionized water to ultrasonically clean the stainless steel mesh for 10 minutes, then put it into an oven and dry it at 70°C for use.

[0069] ② The polyurea coating SHPU prepared in Example 1 was diluted to 10 wt % using DMF, and evenly applied on a stainless steel mesh using a 1 cm wide brush, and then dried in an oven at 70° C. to obtain a stainless steel mesh coated with a polyurea coating (SSM@SHPU).

[0070] ③ Place SSM@SHPU in a 4wt% phytic acid (PA) aqueous solution for ultrasonic assembly for 10 minutes, then add a 2wt% FeCl3 aqueous solution with a volume of 1 / 5 of the phytic acid aqueous solution. After continuing the ultrasonic assembly for 10 minutes, use deionized water to rinse off the unreacted chemicals to obtain a stainless steel mesh coated with polyurea (SSM@SHPU@PA) treated with phytic acid and FeCl3.

[0071] ④ Place SSM@SHPU@PA in a 4wt% PEI aqueous solution and stir for 3h, rinse off the unreacted chemicals with deionized water, and obtain a self-healing oil-water separation membrane (SSM@SHPU@PA@PEI) after drying.

[0072] Figure 1Infrared spectra of the original stainless steel mesh SSM used in step ① of Example 4, SSM@SHPU prepared in step ②, SSM@SHPU@PA prepared in step ③, and SSM@SHPU@PA@PEI prepared in step ④.

[0073] according to Figure 1 It can be seen that 1631cm in SSM@SHPU -1 and 1589cm -1 The C=O peak and NH peak at 1380 cm -1 and 1346cm -1 The CN peaks at 2816 cm -1 The stretching vibration of CH at 1120 cm -1 The stretching vibration of CO at 3417 cm in SSM@SHPU@PA is attributed to the soft segment composed of D2000 in SHPU. -1 and 1120cm -1 The newly appeared -OH broad peak and PO peak are attributed to the phosphate groups in PA. + group, so 3417cm -1 The -NH peak at 1380 cm -1 、1346cm -1 The CN peak at is enhanced.

[0074] Example 9

[0075] This embodiment provides a self-repairing oil-water separation membrane. The only difference between this embodiment and Example 8 is that the SHPU coating prepared in Example 2 is used, and the rest is the same as Example 8.

[0076] Example 10

[0077] This embodiment provides a self-repairing oil-water separation membrane. The only difference between this embodiment and Example 8 is that the SHPU coating prepared in Example 3 is used, and the rest is the same as Example 8.

[0078] Embodiment 11

[0079] This embodiment provides a self-repairing oil-water separation membrane. The only difference between this embodiment and Example 8 is that the SHPU coating prepared in Example 4 is used, and the rest is the same as Example 8.

[0080] Example 12

[0081] This embodiment provides a self-repairing oil-water separation membrane. The only difference between this embodiment and Example 8 is that the SHPU coating prepared in Example 5 is used, and the rest is the same as Example 8.

[0082] Example 13

[0083] This embodiment provides a self-repairing oil-water separation membrane. The only difference between this embodiment and Example 8 is that the SHPU coating prepared in Example 6 is used, and the rest is the same as Example 8.

[0084] Embodiment 14

[0085] This embodiment provides a self-repairing oil-water separation membrane. The only difference between this embodiment and Example 8 is that the SHPU coating prepared in Example 7 is used, and the rest is the same as Example 8.

[0086] Comparative Example 4

[0087] This comparative example provides an oil-water separation membrane. The only difference between this comparative example and Example 8 is that the SHPU coating prepared in Comparative Example 1 is used, and the rest is the same as Example 8.

[0088] Comparative Example 5

[0089] This comparative example provides an oil-water separation membrane. The only difference between this comparative example and Example 8 is that the SHPU coating prepared in Comparative Example 2 is used, and the rest is the same as Example 8.

[0090] Comparative Example 6

[0091] This comparative example provides an oil-water separation membrane. The only difference between this comparative example and Example 8 is that the SHPU coating prepared in Comparative Example 3 is used, and the rest is the same as Example 8.

[0092] Experimental Example 1 SHPU mechanical properties test:

[0093] Trial Groups:

[0094] Group 1: SHPU coating prepared in Example 1;

[0095] Group 2: SHPU coating prepared in Example 2;

[0096] Group 3: SHPU coating prepared in Example 3;

[0097] Group 4: SHPU coating prepared in Example 4;

[0098] Group 5: SHPU coating prepared in Example 5;

[0099] Group 6: SHPU coating prepared in Example 6;

[0100] Group 7: SHPU coating prepared in Example 7;

[0101] Group 8: SHPU coating prepared in Comparative Example 1;

[0102] Group 9: SHPU coating prepared in Comparative Example 2;

[0103] Group 10: SHPU coating prepared in Comparative Example 3;

[0104] Test method:

[0105] The SHPU coatings prepared in each group were filled into a polytetrafluoroethylene mold and dried in an oven at 70°C for 24 hours to prepare SHPU specimens with a size of 50 mm × 6 mm × 1 mm. The SHPU specimens with a size of 50 mm × 6 mm × 1 mm were stretched using a universal material testing machine to test the mechanical properties of each group of SHPU.

[0106] Table 1 Mechanical properties test results

[0107]

[0108] The test results show that the SHPU strips obtained after drying the SHPU coatings prepared in Examples 1-7 all have certain mechanical properties and self-repairing abilities. Among them, the SHPU coating prepared in Example 1 has the strongest mechanical properties and self-repairing abilities. This is because the reasonable ratio of chain extenders can construct a suitable hydrogen bond density and a phase separation structure with obvious soft segment regions and hard segment regions, giving SHPU stronger mechanical properties. The level of mechanical properties after self-repair is often based on the mechanical properties before repair. SHPU with better mechanical properties before repair and containing an appropriate number of dynamic disulfide bonds has better self-repairing abilities.

[0109] The mechanical properties and self-healing ability of the SHPU coating prepared in Comparative Example 1 are poor, because Comparative Example 1 lacks 4,4'-diaminodiphenyl disulfide chain extender and lacks synergistic effect, resulting in no self-healing performance; the mechanical properties and self-healing ability of the SHPU coating prepared in Comparative Example 2 are poor, because the amount of chain extender is large and there are a large number of unreacted amino groups, resulting in poor mechanical properties; the mechanical properties and self-healing ability of the SHPU coating prepared in Comparative Example 3 are poor, because the lack of oxalyl dihydrazide chain extender leads to the disappearance of synergistic effect, the reduction of the number of hydrogen bonds in the material structure, and the aggravation of the free movement and fusion tendency of disulfide bonds, resulting in poor mechanical properties of the material at room temperature.

[0110] Experimental Example 2 Self-repair performance test:

[0111] Self-healing ability refers to the ability of a material to restore its mechanical properties and morphology under certain conditions after being damaged. To test the repair performance of SHPU@PA@PEI, a self-healing experiment was conducted. The test method is as follows: Figure 5As shown, the SHPU coating prepared in Example 1 was filled into a polytetrafluoroethylene mold and dried in an oven at 70°C for 24 hours to obtain a SHPU membrane. The SHPU membrane was placed in a 4wt% phytic acid (PA) aqueous solution for ultrasonic assembly for 10 minutes, and then a 2wt% FeCl3 aqueous solution with a volume of 1 / 5 of the phytic acid aqueous solution was added. After continuing the ultrasonic assembly for 10 minutes, deionized water was used to rinse off the unreacted chemical substances to obtain SHPU@PA. The SHPU@PA was placed in a 4wt% PEI aqueous solution and stirred for 3 hours, and deionized water was used to rinse off the unreacted chemical substances. After drying, a SHPU@PA@PEI membrane was obtained. The SHPU@PA@PEI membrane was cut into small strips, compacted with two glass slides, and self-repaired under 80°C repair conditions. After the repair was completed, the glass slides were removed to obtain a complete SHPU@PA@PEI membrane again, which proved that SHPU@PA@PEI has excellent self-repairing properties and provides the possibility for the oil-water separation material to be reused after damage.

[0112] Experimental Example 3 Self-repair efficiency test:

[0113] Test method:

[0114] The SHPU coating prepared in Example 1 was filled into a polytetrafluoroethylene mold and dried in an oven at 70°C for 24 hours to obtain a SHPU membrane. The SHPU membrane was placed in a 4wt% phytic acid (PA) aqueous solution for ultrasonic assembly for 10 minutes, and then a 2wt% FeCl3 aqueous solution with a volume of 1 / 5 of the phytic acid aqueous solution was added. After continuing the ultrasonic assembly for 10 minutes, the unreacted chemicals were rinsed off with deionized water to obtain a SHPU@PA membrane. The SHPU@PA membrane was placed in a 4wt% PEI aqueous solution and stirred for 3 hours, and the unreacted chemicals were rinsed off with deionized water. After drying, a SHPU@PA@PEI membrane was obtained, and the SHPU@PA@PEI membrane was made into SHPU@PA@PEI strips with a size of 50mm×6mm×2mm.

[0115] The SHPU@PA@PEI strip with a size of 50mm×6mm×2mm was stretched and its self-healing efficiency (SHE) was tested according to the self-healing efficiency formula. The clamping length between the clamps was 20mm, the stretching speed was 60mm / min, and for each sample, the test was repeated 3 times to take the average value. The self-healing efficiency was calculated according to the following formula:

[0116] SHE=F1 / F0×100%

[0117] F0 is the tensile stress of the conventional original SHPU@PA@PEI spline; F1 is the tensile stress after the spline is cut, the cuts are aligned, and it is self-healed at a certain temperature for a certain period of time.

[0118] SHPU@PA@PEI was placed in an air atmosphere at 80°C for different periods of time, and the self-repair efficiency was calculated according to the above formula, as shown in Table 2. It can be seen from Table 2 that the self-repair efficiency generally shows a trend of first increasing and then decreasing with the extension of the repair treatment time.

[0119] Table 2 Changes of self-repair efficiency over time

[0120]

[0121] The best self-healing time of SHPU@PA@PEI is 1 h, and the self-healing efficiency can reach 90.53%. It can be concluded that the best self-healing condition is 1 h at 80 °C.

[0122] Experimental Example 4 Oil-water separation performance test:

[0123] Trial Groups:

[0124] Group 1: SSM@SHPU prepared in Example 8.

[0125] Group 2: SSM@SHPU@PA prepared in Example 8.

[0126] Group three: SSM@SHPU@PA@PEI prepared in Example 8.

[0127] Group 4: SSM@SHPU@PA@PEI prepared in Example 9;

[0128] Group 5: SSM@SHPU@PA@PEI prepared in Example 10;

[0129] Group 6: SSM@SHPU@PA@PEI prepared in Example 11;

[0130] Group 7: SSM@SHPU@PA@PEI prepared in Example 12;

[0131] Group 8: SSM@SHPU@PA@PEI prepared in Example 13;

[0132] Group 9: SSM@SHPU@PA@PEI prepared in Example 14;

[0133] Group 10: oil-water separation membrane prepared in Comparative Example 4;

[0134] Group 11: oil-water separation membrane prepared in Comparative Example 5;

[0135] Group 12: Oil-water separation membrane prepared in Comparative Example 6.

[0136] Test method:

[0137] Each group used syringe barrels and long-tail clips to assemble and build an oil-water separation device. The oil-water separation performance of six different oil and deionized water mixtures, including n-hexane, toluene, kerosene, diesel, gasoline, and petroleum ether, was tested by gravity drive at room temperature. The oil-water separation membranes prepared by each test group were fully moistened with deionized water before use, and then fixed between two plastic barrels. All oil solvents were dyed with Oil Red O.

[0138] Six different oils, including n-hexane, toluene, kerosene, diesel, gasoline, and petroleum ether, were mixed with deionized water in a ratio of (20 mL, V oil: V water = 1:1) to obtain six oil-water mixtures, which were poured from the nozzle above the device. After all the water was separated, wait for 10 seconds. For each sample, the test was repeated 3 times to take the average value. The separation efficiency (SE) and separation flux (SF) were calculated according to formula (1) and formula (2), respectively.

[0139] SE=V1 / V0×100%(1)

[0140] SF=V2 / st(2)

[0141] V0 and V1 represent the oil volume before and after separation (mL); V2 represents the water volume separated and passed through the separation material (mL); s and t represent the effective separation area of ​​the separation material (cm 2 ) and the time taken for oil-water separation (s).

[0142] The test results are shown in Table 3 and Figure 3 , 4 shown.

[0143] Table 3 Separation efficiency and separation flux

[0144]

[0145]

[0146] It can be seen from Table 3 that the SSM@SHPU@PA@PEI prepared in Examples 8-14 has higher separation efficiency and separation flux; in Comparative Example 4, due to the use of a single chain extender, a synergistic effect cannot be produced, the increase in hydrogen bonds changes the phase separation structure of the material, the mechanical properties of the material deteriorate, and the stability of the coating decreases, resulting in a decrease in the separation effect; in Comparative Example 5, due to the excessive addition of a chain extender, a large amount of unreacted substances affect the phase separation structure of the material, the mechanical properties of the material deteriorate, the stability of the coating decreases, and the separation effect decreases; in Comparative Example 6, due to the use of a single chain extender, a synergistic effect cannot be produced, the reduction in hydrogen bonds changes the phase separation structure of the material, the mechanical properties of the material deteriorate, and the stability of the coating decreases, resulting in a decrease in the separation effect.

[0147] like Figure 3 As shown in the figure, the average separation efficiency of SSM@SHPU, SSM@SHPU@PA, and SSM@SHPU@PA@PEI for the six oils is 5.23%, 86.57%, and 98.53%, respectively. Figure 4 As shown: The average separation flux of SSM@SHPU, SSM@SHPU@PA, and SSM@SHPU@PA@PEI for six kinds of oils is 19627.21L / m 2 / h、11436.75L / m 2 / h、11748.67L / m 2 / h. Figure 3 , 4 It can be seen that the present invention uses the chelation effect between phytic acid and iron ions to make them firmly adhere to the surface of SHPU through coordination, hydrogen bonding and other effects, thereby constructing a coating with a certain hydrophilicity on the surface of SHPU.

[0148] In the present invention, since phytic acid is negatively charged and polyethyleneimine is positively charged, the phytic acid is attached to the surface of phytic acid through electrostatic interaction, thereby constructing micro-nanoscale roughness and further increasing the hydrophilicity of the coating.

[0149] Experimental Example 5 Cyclic Separation Performance Test:

[0150] In order to test whether SSM@SHPU@PA@PEI can exert its self-healing performance in oil-water separation, a cyclic separation test was carried out.

[0151] Trial Groups:

[0152] No self-repairing group: SSM@SHPU@PA@PEI prepared in Example 8;

[0153] Self-healing group 1: SSM@SHPU@PA@PEI prepared in Example 8.

[0154] Self-repairing group 2: the oil-water separation membrane prepared in comparative example 4 was used.

[0155] Test method:

[0156] A cyclic separation test was performed on the three groups of materials using an oil-water mixture composed of 10 ml of water and 10 ml of kerosene. During the test, the self-repairing group 1 and the self-repairing group 2 self-repaired at 80°C after 4 cyclic separations each time, and continued to perform cyclic separation after the repair was completed, and continued to perform cyclic separation until the 32nd cycle; the non-self-repairing group continued to perform cyclic separation until the 32nd cycle, without any self-repair treatment in the middle.

[0157] Test results:

[0158] like Figure 2As shown, the cyclic separation efficiency diagram of the self-healing oil-water separation membrane prepared in Example 8 for kerosene / water mixture. In the 32 cyclic separation tests, it can be seen that the separation efficiency of the non-self-healing group and the self-healing group 2 decreased significantly faster than that of the self-healing group 1. After 32 cyclic separations, the separation efficiency of the non-self-healing group decreased by 2.14%, the separation efficiency of the self-healing group 2 decreased by 4.60%, and the separation efficiency of the self-healing group 1 decreased by only 0.87%. After 32 cyclic separations, the separation efficiency of the non-self-healing group SSM@SHPU@PA@PEI was 96.3%, and that of the self-healing group 1 was 97.6%, which was 1.3% higher.

[0159] Through the above experiments, it can be seen that the self-healing oil-water separation membrane prepared in Example 8 contains two chain extenders, ODH and AD, which play a synergistic role in combination, while ensuring the mechanical properties of the coating material, giving the material self-healing ability. The oil-water separation cycle effect of self-healing group 1 is significantly better than that of the non-self-healing group; the oil-water separation membrane prepared in comparative example 4 lacks AD chain extender and cannot produce synergistic effects, so there is no self-healing effect. In addition, the use of a single ODH chain extender leads to a decrease in the mechanical properties of the coating material, which is difficult to withstand multiple flushing of the oil-water mixture, and the oil-water separation cycle effect is poor.

[0160] The embodiments of the present application are described above in conjunction with the accompanying drawings, but the present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of the present application, ordinary technicians in this field can also make many forms without departing from the purpose of the present application and the scope of protection of the claims, all of which are within the protection of the present application.

Claims

1. A self-repairing polyurea coating, characterized in that: The invention is composed of the following raw materials in the following proportions: polyurea prepolymer: solvent: chain extender = 20-60: 15-40: 5-30; The polyurea prepolymer is composed of the following raw materials in the following proportions: Solvent: amino-terminated substance: isocyanate-terminated substance: organotin catalyst = 10-25: 10-30: 20-60: 0.1-1.

2. A polyurea coating according to claim 1, characterized in that: The solvent is dimethylformamide.

3. A polyurea coating according to claim 1, characterized in that: The chain extender is 4,4'-diaminodiphenyl disulfide and oxalyl dihydrazide, and the molar ratio of the 4,4'-diaminodiphenyl disulfide to oxalyl dihydrazide is 3-9:1-7.

4. A polyurea coating according to claim 1, characterized in that: The amino-terminated substance is polyetheramine.

5. The polyurea coating according to claim 1, characterized in that: The terminal isocyanate substance is isophorone diisocyanate.

6. A polyurea coating according to claim 1, characterized in that: The organotin catalyst is dibutyltin dilaurate.

7. The method for preparing the polyurea coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: ① Add terminal amino substances and terminal isocyanate substances to dimethylformamide in sequence, and finally add an organic tin catalyst, and stir in a water bath at 30-60°C for 0.5-3h to obtain a polyurea prepolymer with a long chain structure terminated with an isocyanate group; ② Add dimethylformamide to the polyurea prepolymer, then add a chain extender, and stir in a water bath at 30-60°C for 1-5 hours to obtain a polyurea coating.

8. A self-repairing oil-water separation membrane, characterized in that: The polyurea coating is obtained by compounding the polyurea coating according to any one of claims 1 to 6 with a substrate.

9. The method for preparing the oil-water separation membrane according to claim 8, characterized in that: The following steps are involved: ① dilute the polyurea coating according to any one of claims 1 to 6 to 5-30wt%, evenly apply it on the substrate, and dry it; ②Put it in 1-5wt% phytic acid aqueous solution and perform ultrasonic assembly for 10-30min. ③ Add 1-5wt% FeCl3 aqueous solution with a volume of 1 / 2-1 / 10 of the phytic acid aqueous solution, continue ultrasonic assembly for 10-30 minutes, and then use deionized water to rinse off the unreacted chemicals; ④ Place in a 1-5wt% polyethyleneimine aqueous solution and stir for 1-5h, rinse off the unreacted chemicals with deionized water, and dry.

10. Use of the self-repairing oil-water separation membrane according to claim 7 or 8 in the field of oil-water separation.

Citation Information

Patent Citations

  • Self-repaired oil-water separating material and preparation method thereof

    CN104984564A

  • Crosslinked polyurea elastomer with self-repairing property and preparation method thereof

    CN108559052A

  • Preparation method of ultra-thin anti-contamination composite nanofiltration membrane assembled from phytic acid

    CN109012183A

  • Preparation method of self-extinguishing, super-hydrophilic and underwater super-oleophobic coating

    CN110314829A

  • Pervious concrete for municipal roads and construction method thereof

    CN111943600A